Follow-up study on COVID-19 survivors one year after discharge from hospital. (November 2021) - Zhao, Yumiao; Yang, Chunxia; An, Xiaocai; Xiong, Yajun; Shang, Yaomin; He, Jiarong; Qiu, Yan; Zhang, Ning; Huang, Lisha; Jia, Junli; Xu, Qinfu; Zhang, Long; et al.
Highlights: The prevalence of muscle fatigue and insomnia up to 1 year after COVID-19 was high The prevalence of anxiety or depression up to 1 year after COVID-19 was high Survivors with radiological anomalies were older Survivors with impairment of DLCO had higher urea nitrogen levels The levels of SARS-CoV-2 NAb and IgG at 1 year after discharge were decreased Abstract: Objective: To evaluate the long-term consequences of COVID-19 survivors one year after recovery, and to identify the risk factors associated with abnormal patterns in chest imaging manifestations or impaired lung function. Methods: COVID-19 patients were recruited and prospectively followed up with symptoms, health-related quality of life, psychological questionnaires, 6-minute walking test, chest computed tomography (CT), pulmonary function tests, and blood tests. Multivariable logistic regression models were used to evaluate the association between the clinical characteristics and chest CT abnormalities or pulmonary function. Results: Ninety-four patients with COVID-19 were recruited between January 16 and February 6, 2021. Muscle fatigue and insomnia were the most common symptoms. Chest CT scans were abnormal in 71.28% of participants. The results of multivariable regression showed an increased odds in age. Ten patients had diffusing capacity of the lung for carbon monoxide (DLCO) impairment. Urea nitrogen concentration on admission was significantly associated with impaired DLCO. IgG levels and neutralizing activity were significantly lower compared with those in the early phase. Conclusions: One year after hospitalization for COVID-19, a cohort of survivors were mainly troubled with muscle fatigue and insomnia. Pulmonary structural abnormalities and pulmonary diffusion capacities were highly prevalent in surviving COVID-19 patients. It is necessary to intervene in the main target population for long-term recovery.